Current situation and reflection on care needs and related service models among the elderly (老年人养老需求及照护模式的发展现状及思考) - DUAN Xin (段欣); HUANG Jin (黄金); QIU Tieying (仇铁英) (中西医结合护理)
With the rapid advancement of the population aging, how to precisely meet the needs of the elderly has become an urgent problem. The paper focuses on the current situation and problems of elderly care in China, typical elderly care service models at home and abroad, and the development of domestic elderly care models, with a view to laying the theoretical foundation for constructing a better service model that meets the diversified and personalized service needs of the elderly in China. (随着人口老龄化态势的迅速发展, 如何精准满足老年人的养老需求成为亟待解决的民生问题。本文重点总结了我国老年人的养老现状和问题、国内外典型的养老模式以及现阶段国内养老模式的发展状况, 以期为构建更加符合我国老年人多元化、个性化服务需求的养老模式奠定理论基础。)